IMPLEMENTASI SISTEM TATA KELOLA PELAYANAN JASA CUCI KENDARAAN TERINTEGRASI APLIKASI SOSIAL MEDIA WHATSAPP - Markani Markani; Asrul Halim; Siti Nurhalizah; Neneng Awaliah; Tamra Tamra; Andi Yulia Muniar; First Wanita (Nusantara Hasana Berdikari, 2022)
Maximum service is an absolute thing for agencies or companies, especially those engaged in services. Services will affect the increase or decrease in the performance of a company or agency. One of the companies engaged in vehicle washing services, namely Syainaya Car Wash, still requires a good service management system by utilizing qualified technology. Services at Syainaya Car Wash still use conventional methods so that customer queues are still often confused because the recording system is still manual which results in customers waiting a long time. This study aims to create a governance system for vehicle washing services at Syainaya Car Wash to facilitate cashier services in interacting with employees using WhatsApp media, to make it easier for customers to find out when their vehicle has been washed when the vehicle is left for other matters, and make it easier for leaders in check transaction data and make it easier to calculate employee commissions every week. This data was obtained through, 1) Field research, 2) Direct interviews with the company. This system is made using a sublime text editor application and xampp as a database storage service with the PHP programming language. The results of this study indicate that the implementation of a governance system that is integrated with WhatsApp social media is very user friendly, has an attractive appearance and is easy to understand for both cashiers, managers and customers. Based on the test results using the UAT (User Acceptance Testing) testing technique, 86.8% of 27 respondents obtained results, so that it was declared feasible based on the tests carried out.